Versatile Catalytic Hydrogenation Using A Simple SnIV Lewis Acid - Scott,DJ; Phillips,NA; Sapsford,JS; Deacy,AC; Fuchter,MJ; Ashley,AE (Angewandte Chemie International Edition, 2016)
Despite the rapid development of frustrated Lewis pair (FLP) chemistry over the last ten years, its application in catalytic hydrogenations remains dependent on a narrow family of structurally similar early main-group Lewis acids (LAs), inevitably placing limitations on reactivity, sensitivity and substrate scope. Herein we describe the FLP-mediated H2 activation and catalytic hydrogenation activity of the alternative LA iPr3SnOTf, which acts as a surrogate for the trialkylstannylium ion iPr3Sn+, and is rapidly and easily prepared from simple, inexpensive starting materials. This highly thermally robust LA is found to be competent in the hydrogenation of a number of different unsaturated functional groups (which is unique to date for main-group FLP LAs not based on boron), and also displays a remarkable tolerance to moisture.